Establishment of national diagnostic reference levels for radiotherapy computed tomography simulation procedures in Slovenia. Issue 127 (June 2020) - Zalokar, Nika; Žager Marciuš, Valerija; Mekiš, Nejc
Highlights: Radiotherapy CT localization doses are not insignificant. RT CT simulation doses are generally higher than diagnostic CT. In our study the DLP values were on average higher for 70 % in comparison to diagnostic CT. CT simulation DRLs in RT are established for radiation protection of patients. Abstract: Purpose: To propose national diagnostic reference levels (DRLs) for radiotherapy (RT) computed tomography (CT) localization purposes, compare both CT units used in the largest RT department in the country and to compare gathered results with other published DRLs in order to discover any need of optimization. Methods: In total, 1631 patient data (time spend of 4 months) regarding sex, examination type, total dose-length product (DLP) and CTDIvol was collated on two CT units. Those simulation procedures account for more than 80 % of all simulation procedures performed nationwide. Then, total DLP and CTDIvol was calculated and mean, median and 3 rd quartile for both units together were presented to determine national DRLs for simulation procedures. The same data was later compared between both units to discover any potential need for optimization. Results: 3 rd quartile values of DLP for abdomen, breast, chest, head, head and neck, pelvis and spine were 1116.2, 606.6, 832.4, 1942.4, 969.2, 677.1 and 1042.4 mGy∙cm, respectively. 3 rd quartile CTDIvol values for the same sequence of procedures were 18.7, 13.3, 19.2, 76.9, 22.6, 17.9 and 22.2 mGy, respectively. Among the two units, the mentioned dose values were on average significantly higher on one CT unit than on the other unit. Conclusions: When comparing collected dose values with other studies, RT CT DRLs showed that radiation doses from our institution were similar or even lower. Some variations were found between both CT units in certain protocols, so exposure parameters should be reviewed and optimized.